Leveraging a digital network of pharmacy professionals to test a technology-assisted model to improve pharmacy access to quality-assured COVID-19 rapid antigen tests approved for self-use in Vietnam - Tien Ho; Jaca Maison Lailo; Edrick Ramoran; Karishma Mutreja; Anabel Gomez; Michael Gallo; Josselyn Neukom (PLoS ONE, 2025)
Expanding access to rapid and self-use diagnostics in low-and-middle-income countries (LMICs) is crucial for advancing universal health coverage and creating more self-care opportunities. This study aimed to test the ability of a technology-assisted pharmacy activation model in Vietnam to improve access to quality-assured COVID-19 self-tests through the retail pharmacy channel. SwipeRx, a digital network with more than 30,000 pharmacy professionals in Vietnam, was leveraged to raise awareness about the benefits of COVID-19 rapid antigen tests (Ag-RDTs) that meet quality assurance standards for self-use and were registered with the Vietnamese regulatory authority. The campaigns also included information on local suppliers of Humasis and Flowflex self-test products, offering favorable pricing terms for SwipeRx users. In addition, offline pharmacy training and point-of-sale materials were provided to encourage dispensing, counseling, and restocking of at least one locally registered self-use Ag-RDT for COVID-19. After nine months of engagement between 2022 and 2023, a digital survey was conducted among 331 retail pharmacies to assess the impact on knowledge and practices related to COVID-19 self-tests. Pharmacy professionals who received SwipeRx training reported greater confidence and knowledge in stocking, dispensing, and counseling clients on the proper use of COVID-19 self-tests. These trained professionals were also more capable of distinguishing between COVID-19 Ag-RDTs approved for self-use and those approved for professional use. By the end of the nine months, 70 (92%) of trained pharmacy professionals stocked at least one quality-assured self-test for COVID-19, compared to just 38 (29%) of untrained professionals. These findings demonstrate that digital pharmacy networks can rapidly facilitate market introduction and access to new diagnostic products. Future initiatives should prioritize continuous price negotiations with manufacturers and distributors, focusing on optimizing pricing, credit, and delivery terms for community pharmacies. Additionally, combining digital and offline training with community demand-generating activities could facilitate greater pharmacy uptake of Ag-RDTs and other prioritized public health products.